Septicemia caused by an emerging pathogen, Elizabethkingia miricola, in a laboratory colony of African dwarf frogs (Hymenochirus curtipes). Issue 3 (May 2023) - Yang, Stephanie; Si, Catherine; Mani, Rinosh; Keller, Jill; Hoenerhoff, Mark J.
An outbreak of morbidity and mortality in an African dwarf frog ( Hymenochirus curtipes) colony was reported following arrival at an animal research facility. Animals were found dead on arrival or became moribund shortly thereafter, and additional animals showed clinical signs of lethargy, weight loss, and anorexia over the following 3 weeks. Externally, some affected animals presented with multifocal areas of hyperemia in the inguinal and axillary areas and on the limbs, and mottled tan discoloration along the ventral abdomen. Histologically, lesions were consistent with generalized septicemia, characterized by granulomatous meningitis, otitis media, peritonitis (coelomitis), myocarditis and pericarditis, nephritis, pneumonia, and arthritis. Gram staining identified gram-negative rod-shaped bacteria free within tissues and within macrophages. Culture results of coelomic swabs identified moderate to numerous Elizabethkingia miricola. Testing of water from tanks housing affected animals showed elevated levels of nitrites and ammonia, and the presence of Citrobacter, Aeromonas, Pseudomonas, and Staphylococcus spp. cultured from several tank biofilters. E miricola is a newly recognized and rapidly emerging opportunistic pathogen in anurans and has been reported as a cause of septicemia in humans. This report documents the first occurrence of E. miricola septicemia in African dwarf frogs and illustrates the importance of this potential pathogen in the laboratory setting for amphibian research colonies, as well as those individuals directly working with them.